Pemberdayaan Multidimensi Melalui Program Kesehatan, Ekonomi, dan Lingkungan di Kelurahan Tangkerang Labuai Masyarakat - Al-Muhtadeebillah, Hussein; Manalu, M. Farhan Albetri Nando; Dewi, Mutia; Balqis, Inayah Nazira; Putri, Yufi Karunia; Sintani, Indah; Nadira, Rahima; Dewi, Cindy Vatyka; Akbar, Cindy Raksandy; Manalu, Feby Valentina; Prima, Ryan Ananda; Situmorang, Benyamin Dari Jehuda (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Community Service Activities through the Community Service Program in Tangkerang Labuai aim to address three main issues in the community: health, economy, and environment. In the health sector, stunting prevention was carried out through nutrition and health education, particularly targeting mothers and children. In the economic sector, the development of Micro, Small, and Medium Enterprises (MSME) was supported by registering and training local business owners to use Google Maps to promote business digitalization. In the environmental sector, waste management was implemented through the creation of biopore holes and the production of liquid compost to reduce the amount of organic waste disposed of at Temporary Waste Disposal Sites. The implementation methods included educational, participatory, and appropriate technology-based approaches. The results of these activities indicate an increase in community awareness of stunting prevention, the growth of MSMEs through improved digital access, and a decrease in the volume of waste sent to Temporary Waste Disposal Sites due to biopore holes and composting efforts. This program has brought sustainable positive impacts on the health, economic resilience, and environmental quality of the Tangkerang Labuai community.